GOARN training: supporting field epidemiology trainees to upskill for public health emergency response - Lisson, Yasmin; Allen, Keeley; Stewart, Tony; Parry, Amy (Western Pacific Surveillance and Response, 2024)
This article describes the authors' perspective on the importance of upskilling trainees in field epidemiology training programmes (FETPs) for public health response.
Keywords: epidemiology; emergency; health workforce; education; public health practice; epidemiologists